RELATIONSHIP OF ACTION ON TOOTH BRUSH WITH ORAL HIGIENE STATUS AT BASIC SCHOOL IN PUEDADA BIREUEN DISTRICT - Intan Liana; Anwar Arbi (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
Action is one of the factors that can affect dental health status. Based on the initial survey, 10 children who agreed 4 had moderate teeth and mouth criteria, 6 children had dental hygiene and mouth had poor criteria. The purpose of this study was to study the relationship of action to the status of dental and oral hygiene of fifth and sixth graders of elementary school in Peudada, Bireuen District. This research is analytical with cross sectional design. The population of all fifth and sixth grade students of elementary school in Bireuen District was 50 respondents. The sample of this study is total participants, retrieval of data by conducting interviews and examinations using Chi-Square statistical test (α = 0.05). The results showed the actions of respondents who were categorized as good, had moderate dental and oral hygiene status (P <0.05). Can conclude that there is a relationship between actions with dental and oral hygiene. It is expected that teachers and health workers can assist in guidance and provide guidance on dental and oral hygiene care.